Normalization of Gene expression by quantitative RT-PCR in human cell line: comparison of 12 endogenous reference genes (2018)
BACKGROUND: Polymerase Chain Reaction (PCR) has become an important diagnostic and research tool of modern molecular biology globally. Real-time PCR allows for rapid and reliable quantification of mRNA transcription. Reference genes are used as internal reaction control to normalise mRNA levels between different samples in order to allow for an exact comparison of mRNA transcription level. METHODS: In this study, twelve commonly used human reference genes were investigated in Human Embryonic Kidney Cell Lines (HEK293) using real-time qPCR with SYBR green. The genes included beta-2-microglobulin (B2M), glyceraldehyde-3- phosphate dehydrogenase (GAPDH), succinate dehydrogenase complex subunit A (SDHA), and tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein zeta polypeptide (YWHAZ). The stability of these reference genes was investigated using the geNorm application. RESULTS: The range of expression stability in the genes analysed was (from the most stable to the least stable): UBC, TOP1, ATP5B, CYC1, GAPDH, SDHA, YWHAZ, CTB, 18S, EIFA-2, B2M and RPL13A. The optimal number of reference targets in the experiment was calculated to be 2 (geNorm V<0.15) when comparing a normalization factor based on the 2 or 3 most stable targets). CONCLUSION: The expression stability varied greatly between the 12 candidate reference genes. UBC, TOP1, ATP5B, CYC1 and GAPDH respectively showed the highest stability in HEK293 cells based on both expression stability and expression level. Overall, our data suggest that UBC and TOP1show the least variation and the highest expression stability. This report validates the need for rational selection of reference genes for data normalization to ensure accuracy of quantitative PCR assays.